Succession challenges in maintaining sustainability: Indonesian mining and construction industry - Ivan, Rahadian Firdaus (2022)
The family business is the oldest form of business organisation and is very important in the development of economies around the world. It was found that about 96% of the 165,000 companies established in Indonesia are family businesses and have a contribution to Gross Domestic Product. Topics that become essential issues in family businesses are the problems of family business processes and the sustainability of family businesses after succession or transition from the first generation to the next generation. In Indonesia, there are only 13% of companies have a robust and formalised plan. Another 39% have fewer formal plans, while 35% have no plans at all. The mining industry is one sector that contributes to the rapid growth of Indonesia's market capitalisation. The value of GDP generated from industrial mining in Indonesia reaches $13.8 million and is the highest in Southeast Asia.